HER2-positive pure mucinous breast carcinoma: A case report and literature review. Issue 33 (14th August 2020) - Zhao, Xingjuan; Yang, Xuan; Gao, Runfang; Zhai, Liqin; Yang, Lizhu; Yu, Keda
Abstract: Introduction: Pure mucinous carcinoma is a rare type of breast carcinoma, but it usually has a favorable prognosis. Tumors of pure mucinous carcinoma are typically positive for both estrogen receptor (ER) and progesterone receptor (PR), and they do not commonly overexpress human epidermal growth factor receptor 2 (HER2). However, when tumors have HER2 overexpression and are progesterone receptor negative, the prognosis is worse. Patient concerns: A 59-year-old female reported a slow growth mass of 3 years, which was radiologically diagnosed as fibroadenoma at another institution. The patient came to our institution for treatment and follow-up. She had no salient past history. Diagnosis: Excisional biopsy revealed a pure mucinous breast carcinoma that was ER (100%, moderate-strong intensity), PR(−), 5% Ki-67 (+), and HER2(3+) by immunohistochemistry. The HER2 gene was found to be amplified by fluorescence in situ hybridization (FISH). The clinical staging was T2N0M0, with pathological grade I, subtype luminal B. Interventions: After a modified radical mastectomy, she received four 21-day cycles of intravenous docetaxel (75 mg/m 2 ), intravenous cyclophosphamide (600 mg/m 2 ), and intravenous trastuzumab (8 mg/kg) (loading dose) on day 1 followed by 6 mg/kg every 3 weeks to complete a full year of treatment. She then received 2.5 mg of letrozole daily for 5 years. Outcomes: After following up for 2 years, the patient's outcome was survival without recurrence. Cardiac ultrasounds were performed every 3 months and there was no change in the left ventricular ejection fraction (LEVF). Conclusion: It is essential to correctly diagnose the ER(+), PR(−) HER2(+) subtype in mucinous carcinoma. This type should be treated with chemotherapy and anti-HER2 therapy, as well as aromatase inhibitor endocrine therapy.